Optimasi Pembentukan Gula Cair Dari Limbah Kulit Singkong (Manihot utilisima Pohl) Oleh Bacillus Licheniformis dalam Usaha Menumbuhkan Jiwa Kewirausahaan. - Budiarti, Retni S; Harlis, Harlis; Kapli, Hari (Universitas Jambi, 2018)
This study aims to determine the optimal concentration of Bacillus licheniformis required in the formation of liquid sugar from cassava waste, the value of sugar and value starch contained in degraded cassava skin waste. The design used in this study was Completely Randomized Design (RAL) with 4 treatment concentration of cassava leaf extract (Manihot utilissima Pohl.), Ie 0 concentration, 1.5 ml concentration, 2.5 ml concentration and 3.5 ml of concentration B. licheneformis. Data were analyzed using analisis (ANOVA) followed by Duncan's range test (DMRT) with a 5% confidence level. The results of the study showed that all treatments had a significant effect on the administration of B. licheniformis concentrations. Treatment using 1.5 ml B. licheniformis concentration on cassava skin substrate weighing 1 gram after Duncan's test range (DMRT) with 5% confidence level resulted Reduction sugar value of 6.07%.